Arsenic and Mercury Containing Traditional Chinese Medicine (Realgar and Cinnabar) Strongly Inhibit Organic Anion Transporters, Oat1 and Oat3, In Vivo in Mice. (16th December 2015) - Yu, Wen-Hao; Zhang, Na; Qi, Jin-Feng; Sun, Chen; Wang, Yong-Hui; Lin, Mei
Abstract : Toxic heavy metals, including mercury (Hg) and arsenic (As), accumulate preferentially in kidneys and always cause acute renal failure. The aim of this study was to investigate whether these samples affect organic anion transporters, Oat1 and Oat3, in vivo in mice kidney. Mice (n = 1 0 ) were orally treated with investigational samples. After last administration, all mice were i.v. p -aminohippuric acid (PAH), and the blood and kidneys samples were collected. The concentrations of PAH were quantified by spectrophotometry. mRNA expressions of Oat1 and Oat3 were assayed by real-time PCR. In comparison with corresponding control, major pharmacokinetic parameters of PAH in sera were significantly changed by investigational samples (p < 0.05 ), PAH accumulations in the kidney tissues were significantly higher (p < 0.05 ), PAH uptake by renal slices was greatly reduced, Oat1 and Oat3 mRNA expression were significantly inhibited in investigational sample groups. Arsenic and mercury containing traditional Chinese medicine (Realgar and Cinnabar) probably induce kidney damage through inhibiting several members of the organic anion transporters (such as OAT1 and OAT3).